2017
DOI: 10.3390/ijms18051061
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Autophagy in Sertoli Cells of Ethanol-Treated Rats Is Associated with Induction of Inducible Nitric Oxide Synthase (iNOS), Androgen Receptor Suppression and Germ Cell Apoptosis

Abstract: This study was conducted to investigate the autophagic response of Sertoli cells (SCs) to acute ethanol toxicity using in vivo and in vitro models. Adult Wistar rats were intraperitoneally injected with either 5 g/kg ethanol or phosphate-buffered saline (for the control group) and sacrificed 0, 3, 6 and 24 h after injection. Compared to the control group, enhanced germ cell apoptosis was observed in the ethanol-treated rats (ETRs) in association with upregulation of iNOS and reduced expression of androgen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 62 publications
(151 reference statements)
6
50
0
Order By: Relevance
“…In contrast, the induction of the meiosis gatekeeper STRA8 at the onset of meiosis is associated with a repression of autophagy and with ULK1 and TFEB downregulation ( Ferder et al, 2019 ). In Sertoli cells, TFEB mediates the initiation of autophagy upon exposure to toxins such as ethanol, in order to promote cell survival and sustain spermatogenesis ( Horibe et al, 2017 ). Interestingly, ULK1 directly relates autophagy with the mTOR pathway, which regulates many metabolic processes and essential cell functions in response to the nutrient and energy status of the cell ( Kim et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the induction of the meiosis gatekeeper STRA8 at the onset of meiosis is associated with a repression of autophagy and with ULK1 and TFEB downregulation ( Ferder et al, 2019 ). In Sertoli cells, TFEB mediates the initiation of autophagy upon exposure to toxins such as ethanol, in order to promote cell survival and sustain spermatogenesis ( Horibe et al, 2017 ). Interestingly, ULK1 directly relates autophagy with the mTOR pathway, which regulates many metabolic processes and essential cell functions in response to the nutrient and energy status of the cell ( Kim et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, autophagy is characterized by the formation of isolation membranes that engulf a region of the cell forming early AVs or autophagosomes, which are mediated by LC3 (a specific autophagosome marker). The latter then fuse with lysosomes to form late AVs or autolysosomes, and the contents are degraded by cathepsins [3,4]. Autophagy may be a selective process in the clearance of damaged mitochondria (mitophagy) or excessive lipid droplets (lipophagy) in hepatocytes in association with exposure to acute or chronic ethanol intake.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, germ cells and spermatozoa, in particular, depend on lactate production by SCs via autophagy and glycolysis for viability and motility under normal and stressed conditions [10,11]. Fifth, autophagy upregulation has been found to be a prosurvival mechanism for cultured SCs upon exposure to heat stress [11] or high dose of ethanol [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…receptor expression in testis (Horibe et al, 2017;Horibe, Eid, Ito, Otsuki, & Kondo, 2019). It has been also demonstrated that testicular proteins such as steroidogenic acute regulatory (StAR) protein (Jana, Jana, De, & Guha, 2010;Radhakrishnakartha, Appu, & Indira, 2014) and cytochrome P450 side-chain cleavage enzyme (P450scc) are lower expressed in ethanol animals (Radhakrishnakartha et al, 2014).…”
mentioning
confidence: 99%